2008
DOI: 10.1016/j.febslet.2008.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of the cytopathic effect induced by Clostridium difficile Toxin B by active Rac1

Abstract: Clostridium difficile Toxin B (TcdB) glucosylates low molecular weight GTP-binding proteins of the Rho subfamily and thereby causes actin re-organization (cell rounding). This ''cytopathic effect'' has been generally attributed to RhoA inactivation. Here we show that cells expressing non-glucosylatable Rac1-Q61L are protected from the cytopathic effect of TcdB. In contrast, cells expressing RhoA-Q63L or mock-transfected cells are fully susceptible for the cytopathic effect of TcdB. These findings are extended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 41 publications
2
38
0
Order By: Relevance
“…The cellular state of Ras proteins must be taken into account if studies on TcsL are performed in cells expressing oncogenic (GTP-bound) Ras including many fibroblast lines. Small GTPases in general are preferably glucosylated in their GDP-bound state but (at least transiently) protected from glucosylation in their GTP-bound state [7,13]. One must expect that Ras transformed fibroblasts exhibit a lower sensitivity to TcsL-induced Ras glucosylation than to Rac1 glucosylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cellular state of Ras proteins must be taken into account if studies on TcsL are performed in cells expressing oncogenic (GTP-bound) Ras including many fibroblast lines. Small GTPases in general are preferably glucosylated in their GDP-bound state but (at least transiently) protected from glucosylation in their GTP-bound state [7,13]. One must expect that Ras transformed fibroblasts exhibit a lower sensitivity to TcsL-induced Ras glucosylation than to Rac1 glucosylation.…”
Section: Discussionmentioning
confidence: 99%
“…While TcsH specifically glucosylates Rho proteins, TcsL glucosylates Rac as well as the Ras family proteins (H/K/N/R)Ras, Rap(1/ 2), and Ral [9][10][11][12]. Treatment of cultured cells with TcsL results in actin re-organization (''cytopathic effect"), that is likely based on Rac1 glucosylation [13]. TcsL further causes apoptotic cell death (''cytotoxic effect"), likely based on the inhibition of (H/K/N)Ras/ phosphatidylinositide 3 0 -OH kinase (PI3 K)/Akt survival signaling [10,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the isomeric TcdB from the variant C. difficile serotype F strain 1470 (TcdBF) that glucosylates Rac1 but not RhoA, has a cytopathic effect (13). Halabi-Cabezon et al (10) reported that the glucosylation of Rac1 rather than RhoA correlates with the cytopathic effect of TcdB. It has been reported that Rac1 plays a critical role in the organization of the actin cytoskeleton (3).…”
Section: Discussionmentioning
confidence: 99%
“…In part, this is due to actin reorganization and consequent inhibition of contractile ring formation in cytokinesis triggered by Rho glycosylation, leading to binucleation and cell cycle arrest at the G 2 -M level (11,(13)(14)(15)(16). TcdA and TcdB also block the G 1 -S transition (10,12).…”
mentioning
confidence: 99%